ANALYSIS OF TANNIN COMPOUNDS IN TURMERIC RHIZOMES (CURCUMA LONGA L.) USING UV-VIS SPECTROPHOTOMETRY - Chaerani Chaiis; Lintang Suci Ayu; Celsi andriyani; Siti Mupti Zaenul Inzi; Elvira Atriyani; La Ode Akbar Rasydy (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the levels of tannin compounds in fresh and dried turmeric (Curcuma longa L.) rhizomes using the UV-Vis spectrophotometric method. Tannins are phenolic compounds that have important biological activities, such as antioxidant, antimicrobial, and anti-inflammatory. Turmeric rhizome samples were extracted using 96% ethanol solvent by maceration method for three days. Analysis was performed using Folin-Ciocalteu reagent and saturated sodium carbonate solution to form colored complexes measured at a maximum wavelength (λ max) of 706 nm. Quantification was performed by comparing the absorbance results against the gallic acid standard calibration curve, which showed a linear relationship with a coefficient of determination (r²) value of 0.9955. The results showed that fresh turmeric rhizomes had higher tannin levels (57,046 mg GAE/g) than dried turmeric (29,005 mg GAE/g). Qualitative and quantitative analysis showed that the UV-Vis spectrophotometric method was effective for detecting and measuring tannin content accurately and sensitively. In addition, the measurement principle based on the Lambert-Beer law, as well as the use of a spectrophotometer with accurate specifications supports the validity of the results. Literature review from Google Scholar, PubMed, and ScienceDirect of ten supporting journals corroborated that this method has been widely applied for the analysis of phenolic compounds in various natural materials. Thus, This study concluded that turmeric rhizome is a potential source of tannins and the UV-Vis method can be used as a reliable phenolic analysis tool in the pharmaceutical and food fields.